Interactive Effects of Vermicompost and Seed Tuber Size On the Production of Potato (Solanum Tuberosum L.) (Bangladesh Journal of Botany, 2021)
An experiment was conducted to find out the effect of vermicompost and seed tuber size on the yield of Potato. The experiment consisted of two factors, i.e., factor A: Vermicompost level (Vc-4): Vc1: 0 t/ha, Vc2: 3 t/ha, Vc3: 6 t/ha and Vc4: 9 t/ha; factor B: Tuber size (T-5): T1: 5 - 10 g, T2: 10 - 20 g, T3: 20 - 30 g, T4: 30 - 40 g and T5: >40 g. Vermicompost was found to have a significant effect on most of the yield contributing parameters. Results showed that yield parameters increased with increasing vermicompost level irrespective of tuber size. Among the 20 treatment combinations, vermicompost @ 9 t/ha with tuber size > 40 g produced the maximum yield (31.33 t/ha) that was 216.82% higher than Vc1T1.Bangladesh J. Bot. 50(3): 695-700, 2021 (September)